THE EFFECT OF GIVING ILL-STRUCTURED MATH PROBLEM AND WELL-STRUCTURED MATH PROBLEM ON THE SELF-EFFICACY OF JUNIOR HIGH SCHOOL STUDENTS - Rahmasari, Indri Aninda; Susanah, Susanah (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
This study aimed to determine the effect of giving ill-structured problems and well-structured problems to students' self-efficacy. The study population was class VIII students at Junior High School 1 Ngawen Blora which consisted of an experimental class and a control class with the selection of samples using purposive sampling technique. This research is a quantitative research with a comparative problem formulation that compares the increase in self-efficacy between students who are given well-structured math problems and ill-structured math problems. The data analysis technique used was t-test dependent and t-test independent. The results showed that: 1) there is an effect of giving ill-structured math problems on students' self-efficacy at a significant level of 0.05; 2) there isn’t an effect of giving well-structured math problems on students' self-efficacy at a significant level of 0.05; 3) there is a difference in changes in student self-efficacy between giving ill-structured math problems and giving well-structured math problems at a significant level of 0.05